Is East Turning to the East? - E. O. Shebalina (Vestnik MGIMO-Universiteta)
Book Review: A.A. Mikaelyan, V.M. Morozov. 2023. The Evolution of Israeli-Chinese and IsraeliIndian Relations. Moscow: MGIMO-University. 213 p.